Diagnóstico de la existencia y uso de las maquinarias agrícolas y aperos agrícolas en el Cantón Vinces, Provincia de Los Ríos en el año 2025 - Carbo García, Carmen Mercedes (2025)
The purpose of the research is to know the diagnosis and the existence of agricultural machinery and implements in the Vinces canton that allows producers to contribute to reducing labor when carrying out cultural tasks and achieving better yields in their productions. To carry out the research, the producers with short-cycle crops in the Vinces canton, parishes and surrounding areas will be considered as the population. To determine the number of samples, the information obtained in response to the letter delivered to those in charge of the offices will be used. of MAGAP-Babahoyo, as a result of the universe population that was obtained was 1,100 producers. The methodology to carry out the research will be posed through a questionnaire based on three aspects, which will allow obtaining results that help solve the problem of the study. Subsequently, producers in the canton and its surroundings will be surveyed. Finally, the information that was obtained will be taken to a calculation table in the Excel program, and with this, perform the calculations of the descriptive statistics that are necessary to have the results in accordance with the objectives set and draw the conclusions and make the respective recommendations.